Medical researchers in non-english countries and concerns about unintentional plagiarism. - Hosseini, Mehrdad Jalalian; Bazargani, Reyhaneh; Abd Latiff, Latiffah; Hanachi, Parichehr; Syed Hassan, Syed Tajuddin; Othman, Mohd Shahwahid (Tehran University of Medical Sciences, 2009)

(untitled)
In this article the author discusses the different methods to avoid plagiarism considering that non-English medical researchers desire their works published in English language journals. The physicians at blood transfusion in Iran reveals that researchers have problems on English writing which leads to zero knowledge of strategies in avoiding plagiarism. It has been suggested that providing an explicit warning and the use of plagiarism detection software are efficient to avoid plagiarism.